Macrolides and COVID-19: An optimum premise - Al-Kuraishy, HayderM; Al-Naimi, MarwaS; Lungnier, ClaireM; Al-Gareeb, AliI (Biomedical and Biotechnology Research Journal, 2020)
The epidemic of coronavirus infection disease 19 (COVID-19), which started in Wuhan City, is caused by severe acute respiratory syndrome coronavirus (SARS-CoV-2) which binds angiotensin-converting enzyme 2 (ACE2) receptor, which is highly expressed by the lung epithelial cells. In COVID-19-induced acute respiratory distress syndrome, a hyperinflammatory syndrome with hypercytokinemia leads to acute lung injury and the development of respiratory failure. Macrolides are broad-spectrum, bacteriostatic antibiotics with significant anti-inflammatory and immunomodulatory effects. Different preclinical and clinical studies have shown that macrolides inhibit cytokine release, attenuate the inflammatory response, and improve immunoglobulin response. Azithromycin potentiates the anti-SARS-CoV-2 activity of chloroquine in COVID-19. However, azithromycin alone is effective initially in the management of COVID-19 due to its antiviral and anti-inflammatory activity. The antiviral potential of azithromycin is linked to different mechanisms, including modulation of lysosomal activity and the interaction points between SARS-CoV-2 and ACE2 receptor. Therefore, macrolides, chiefly azithromycin, are an effective drug against COVID-19 through direct antiviral effect or via the modulation of hyperinflammatory status.